Canning Paradise - Pollet, Olivier (Australia, 2012)
Decades of overfishing by the global tuna industry have now pushed the final frontiers to the waters of Papua-New-Guinea. This high demand for tuna comes at a cost – a human cost, which now affects some of the last places on earth previously untouched by globalization. This film follows the struggle of indigenous tribes to protect their sacred way of life, guarded by traditions dating back thousands of years. The question still remains: does industrialization end poverty?
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films